"We defend Western civilization": Serbian representations of a cartoon conflict - Erjavec, Karmen (Islam and Christian-Muslim relations, 2008)
This article explores how young Serbian intellectuals interpret and further recontextualize the global reactions to the publication of the cartoons of the Prophet Muhammad. On the basis of in-depth interviews and critical discourse analysis, we show how the Serbian mainstream discourses frame the ‘cartoon crisis’ in a specific way—Muslims are labeled as ‘fundamentalists’ and ‘terrorists’. The article argues that this provides a historical excuse to justify and legitimize the violent Serbian policies against the Bosnian and Kosovo Muslims during the 1990s. Furthermore, the informants appropriate the Muslim reactions by using an analogy: they draw parallels between violent global Muslim demonstrations caused by the publication of the cartoons and violent Muslim military attacks against the Serbs in Bosnia and Kosovo.